Direct Torque Control of Induction Motor Drive for PV Array Water Pumping system - LAIB Mohammed Lakhdar; AMANI Aymen; BOUALLAGA Aymen (University of Shahid Hama Lakhdar - El Oued, 2024)
The limited access to electricity poses significant challenges for water security, particularly in isolated desert regions. This thesis proposes a standalone solar-powered water pumping system as a low-maintenance solution. The system comprises a photovoltaic generator connected to a DC-DC boost converter, followed by a voltage source inverter (VSI) driving an induction motor coupled to a centrifugal pump. To optimize energy extraction under varying climatic conditions, Direct Torque Control (DTC) is employed to regulate the induction motor. Additionally, Maximum Power Point Tracking (MPPT) algorithms, specifically Perturb and Observe (P&O) and Incremental Conductance (INC), are implemented to generate the appropriate reference signal for the VSI. This work presents the system design, analyzes its performance using MATLAB/SIMULINK simulations, and verifies its effectiveness in delivering reliable water pumping functionality. ويشكل الوصول المحدود للكهرباء تحديات كبيرة للأمن المائي، خاصة في المناطق الصحراوية المعزولة. تقترح هذه الأطروحة وجود مياه مستقلة تعمل بالطاقة الشمسية نظام الضخ كحل منخفض الصيانة. يشتمل النظام على مولد كهروضوئي متصل بمحول تعزيز DC-DC، متبوعًا بعاكس مصدر الجهد (VSI) الذي يقود المحرك التعريفي إلى جانب مضخة الطرد المركزي. لتحسين استخراج الطاقة تحت متفاوتة الظروف المناخية، يتم استخدام التحكم المباشر في عزم الدوران (DTC) لتنظيم المحرك التعريفي. بالإضافة إلى ذلك، فإن خوارزميات الحد الأقصى لتتبع نقاط الطاقة (MPPT)، وتحديدًا Perturb و يتم تنفيذ المراقبة (P&O) والتوصيل المتزايد (INC) لإنشاء الإشارة المرجعية المناسبة لـ VSI. يعرض هذا العمل تصميم النظام، ويحلله الأداء باستخدام محاكاة MATLAB/SIMULINK، والتحقق من فعاليتها في توفير وظيفة ضخ المياه موثوقة
Master's theses: specializing Electrical control
Keywords: Induction Motor; Direct Torque Control (DTC); Inverter; Photovoltaic; Centrifugal Pump; Solar Energy; Maximum Power Point Tracking (MPPT).; المحرك التعريفي، التحكم المباشر في عزم الدوران (DTC)، العاكس، الكهروضوئية، الطرد المركزي المضخة، الطاقة الشمسية، تتبع نقطة الطاقة القصوى (MPPT).